Co-Operative Pain Education and Self-management (COPES) Expanding Treatment for Real-World Access (ExTRA): Pragmatic Trial Protocol. (10th December 2020) - Heapy, Alicia A; Driscoll, Mary A; Buta, Eugenia; LaChappelle, Kathryn M; Edmond, Sara; Krein, Sarah L; Piette, John D; Mattocks, Kristin; Murphy, Jennifer L; DeBar, Lynn; MacLean, R Ross; Ankawi, Brett; et al.
Abstract: Background: Given access barriers to cognitive behavioral therapy for chronic pain (CBT-CP), this pragmatic superiority trial will determine whether a remotely delivered CBT-CP intervention that addresses these barriers outperforms in-person and other synchronous forms of CBT-CP for veterans with musculoskeletal pain. Design: This pragmatic trial compares an asynchronous form of CBT-CP that uses interactive voice response (IVR) to allow patients to participate from their home (IVR CBT-CP) with synchronous CBT-CP delivered by a Department of Veterans Affairs (VA) clinician. Veterans (n=764; 50% male) with chronic musculoskeletal pain throughout nine VA medical centers will participate. The primary outcome is pain interference after treatment (4 months). Secondary outcomes, including pain intensity, depression symptom severity, sleep, self-efficacy, and global impression of change, are also measured after treatment. Where possible, outcomes are collected via electronic health record extraction, with remaining measures collected via IVR calls to maintain blinding. Quantitative and qualitative process evaluation metrics will be collected to evaluate factors related to implementation. A budget impact analysis will be performed. Summary: This pragmatic trial compares the outcomes, cost, and implementation of two forms of CBT-CP as delivered in the real-world setting. Findings from the trial can be used to guide future policy and implementation efforts related to these interventions and their use in the health system. If one of the interventions emerges as superior, resources can be directed to this modality. If both treatments are effective, patient preferences and health care system factors will take precedence when making referrals. Implications of COVID-19 on treatment provision and trial outcomes are discussed.